(untitled) (Research, Society and Development, 2022)
The work aims to present the main aspects related to the principle of access to justice with regard to the reality of its gratuitousness. Thus, the analysis of the affirmation of access to justice and legal assistance in the Federal Constitution and in the Code of Civil Procedure was carried out, in order to demonstrate that there is still inefficiency of access to justice, specifically when related to free legal assistance, and especially in relation to the Public Defender’s Office, both nationally and in the State of Paraná. At the end, it questioned points related to the aforementioned principle that are believed not to move towards its effectiveness, and which may, in fact, move in the opposite direction to the expected legal certainty, as well as to the sense of justice of the jurisdiction. For that, the deductive method was used, from a general concept of the principle of access to justice and its particular effectiveness when analyzing the gratuitousness of justice. The study is also based on graphic and documental analysis, in addition to bibliographical research, with descriptive and exploratory methodological objective, using the work “O Acesso ao Justiça” as a theoretical reference, as well as the drafts of the Constitution and proposals for amendments.